To solve this system of equations using the elimination method, we can multiply the second equation by 7 to eliminate y.
9x - 7y = 22
7x + 21y = -168
Adding these two equations together, we get:
16x + 14y = -146
=> 8x + 7y = -73
Now we have two equations:
9x - 7y = 22
8x + 7y = -73
Adding these two equations together, we get:
17x = -51
x = -51/17
x = -3
Substitute x = -3 into the first equation:
9(-3) - 7y = 22
-27 - 7y = 22
-7y = 49
y = -49/7
y = -7
Therefore, the solution to the system of equations is (-3, -7).
Use the elimination method to solve the follow system of equations.
9x−7y=22
x+3y=−24
This question requires you to show your work.
(1 point)
Responses
(4, 2)
(4, 2)
(0,−8)
open paren 0 comma negative 8 close paren
(3,−9)
open paren 3 comma negative 9 close paren
(−3,−7)
1 answer